Efek Pelemahan Nilai Tukar Rupiah Terhadap Kinerja Ekspor Indonesia Tahun 2010-2017 - ali, didik rosadi (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
This study aims to analyze the effects of the weakening of the Rupiah exchange rate on Indonesia's export performance. The data used is quarterly period data from 2010 until 2017. The statistical method to analyze the data is Error Correction Model (ECM) method by firstly testing stationeritas to all variables used is the value of Gross Domestic Product (GDP), value exports and exchange rate of Rupiah to US Dollar and test the classical assumption of regression on each model formed. From the estimation result, it is found that in the period of 2010/Q1-2017/Q4 both in long-term and short-term model, the exchange rate effect on export of Indonesia performance is not significant